PERLINDUNGAN HUKUM TRANSAKSI BISNIS INTERNASIONAL TERHADAP KONTRAK TRANSAKSI ELECTRONIC COMMERCE (E-COMMERCE) - Anthony Willyus Wongkar; Endison Ravlindo; Jesselyn Valerie Herman; Jennyver Willyanto (Jurnal Hukum Adigama, 2021)
In this era of globalization, most people in the world are leaving conventional ways to electronic transactions. E-commerce is one of the electronic transactions that is very supportive in the field of economics, especially international business transactions. International business transaction is a study of private law which provides bigger opportunities to each party to make, agree on, and implement the clauses they make. With various technological advances, the world gives chances to international society to make connections between them. In line with this advantage, it is possible that there are deficiencies which will cause problems between those contract makers.  These problems could arise because of the differences between them, such as in terms of culture, legal perspective, and others. Therefore, the different countries' parties should understand about the contract they make and be concerned about the applicable law in the other’s country before making a certain contract. To prevent unwanted legal consequences, an understanding of clear legal protection is needed. The method of this research is a legal normative research with a statutory approach.